CHARACTERIZATION OF BIS-SALICYLALDEHYDE O-PHENYLENEDIAMINE SCHIFF BASE AND ITS DY(III), GD(III), ND(III) AND SM(III) LANTHANOIDS COMPLEXES - MAHMUD, SARATU; Birnin-Yauri, U. A.; Liman, M. G. (FUDMA Journal of Sciences, 2023)
Schiff bases have versatile chemical properties and numerous utilities in various industries consequent of their excellent coordination ability with numerous metal ions especially transition metals. To further exploit the chemical versatility of this promising compound, we thoroughly characterize the aged long synthesized Schiff base; Bis-salicylaldehyde o-phenylenediamine (Salphen) and its Lanthanoid (III) complexes of Neodymium, Samarium, Gadolinium and Dysprosium using solubility test, melting and decomposition analysis, FTIR, Uv-visible spectroscopy, conductivity measurement, elemental analysis, magnetic susceptibility and NMR. The Salphen ligand was soluble in chloroform and carbon tetra chloride among others while its complexes were not soluble in most common organic solvents tested. The melting point of Salphen was 1650C while its Lanthanoid (III) complexes decompose in the range of 210-2410C. The FTIR spectral patterns analysis of the ligand and its complexes conforms to fundamental vibration modes within the structure. Salphen and its Lanthanoid (III) complexes had low conductivity and were paramagnetic, non-hygroscopic and formed binuclear bridged structure with Metal: Ligand ratios of 2: 3. Series of characterization undertaken confirmed the formation of the bridged structured complex between Salphen and Lanthanoid (III) ions with high thermal stabilities, insolubility in most common organic solvents and poor electric conductance.